Design of Soil pH Measuring Instruments Using pH Meter Sensor Module V1.1 SEN0161 Based on Arduino Uno - Yakin, Gusnul H; Satriya Wibawa, I Made; Putra, I Ketut (BULETIN FISIKA; Vol 22 No 2 (2021): BULETIN FISIKA August Edition, 2021)
It has been successfully made a soil pH measuring instrument using pH meter sensor module V1.1 SEN0161 based Arduino Uno. The pH result is measured through the output of the pH meter sensor output value read by the 16-bit ADC. Measurement results are displayed on a 2x16 LCD. The results of calibration test tools performed against standard measuring instruments obtained regression equation y = 0.0012x - 4.0768 with x is the output of sensor output value with accuracy level includes an average deviation of 0.13 and tool precision value of 97.98%. The results of calibration test tools carried out show the measuring instruments made have a good validity (accuracy and precision).